Meta-analysis of the efficacy of preoperative biliary drainage in patients undergoing liver resection for perihilar cholangiocarcinoma - Mehrabi, Arianeb; Khajeh, Elias; Ghamarnejad, Omid; Nikdad, Mohammadsadegh; Chang, De-Hua; Büchler, Markus W.; Hoffmann, Katrin (European journal of radiology, 2020)
Purpose - A systematic review was performed to evaluate the effect of preoperative biliary drainage (PBD) on outcomes after liver resection in perihilar cholangiocarcinoma (PHCC) patients. - Method - MEDLINE and Web of Science were searched up to March 2019. All studies assessing morbidity, mortality, or recurrence in patients who received PBD and hepatectomy for PHCC were included. Mantel-Haenszel tests with a random-effects model were used for meta-analysis. - Results - Sixteen studies involving 2162 patients were included. PBD was associated with higher major morbidity odds ratio [OR] = 1.51; 95 % confidence interval [CI] = 1.14-2.00). Selecting patients for PBD based on simple selection criteria was associated with significantly higher major morbidity (OR = 1.57; 95 % CI = 1.10-2.25). In contrast, selecting patients for PBD according to strict criteria resulted in lower major morbidity compared with patients without PBD (OR = 0.51; 95 % CI = 0.18-1.42). PBD did not influence mortality (OR = 1.06; 95 % CI = 0.70-1.61). Tumor recurrence was significantly higher in the PBD group (OR = 2.07; 95 % CI = 1.38-3.11). To decrease PBD-related complications, the duration between PBD and hepatectomy should be shorter than two weeks. Most reports described PBD on the future liver remnant side. - Conclusions - Routine PBD cannot be recommended but it may be useful in highly selected patients suffering from cholangitis, malnutrition, and long lasting jaundice, for whom an extended hepatectomy is planned. However, However, routine PBD cannot be recommended due to higher morbidity rate after hepatectomy clear patient selection criteria can be defined for PBD in future multicenter randomized controlled studies.
Gesehen am 17.04.2020